MSME Marketing Strategy Analysis to Face Competition in Digitalization Era (Study on MSME Traders Clothing at Pasar Johar MAJT Semarang) - Tri Widiastuti; Dina Kharisma (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2023)
Study this aim analyze online strategy marketing based on strengths and weaknesses, opportunities, and threats on trader clothes at Johar MAJT market Semarang to increase power competitiveness and sales. The research study uses a qualitative descriptive approach. Data were obtained from in-depth interviews with key informants. The research place is in Johar MAJT Market, Semarang, and the research informants are merchant clothing at the Johar MAJT market, Semarang. Data collection techniques through observation, interviews, and documents. Technique analysis data use Miles and Huberman’s model include: 1) reduction,2) presentation. 3) conclusion and verification. Test validity uses credibility tests through technique triangulation technique and source. The results of the study can be concluded that online marketing can increase the power of competitive trader clothes at the Johar MAJT. The online marketing strategy is determined by a combination factor internal and external. In general trader clothes are in quadrant 1, progressive strategy is recommended (Strength-Opportunity -SO) and the company is in very good condition so there are a lot of opportunities to expand continually, increase growth and achieve progress maximum. Strategy Strength-Opportunity (SO) includes: 1) Utilise whole strength in conducting effective communication with consumers, 2) Expanding network by collaborating with marketplaces like Tokopedia, Blibli, Shoppee, and others, so that online sales can increase, 3) Expansion strategy: open outlet new, accept many resellers, 4) Push the price and give a discount product which often searching for community/new product as promotion,5) Cooperate with a distributor so that stock goods always available.